2011
DOI: 10.1007/s13534-011-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and osteoblast cell response on TiN- and TiAlN-coated Ti implant

Abstract: Purpose The purpose of this study was to evaluate the surface characteristics and osteoblast cell response of TiN and TiAlN coated on Ti Surface. Methods TiN and TiAlN coatings were applied on Ti dental implant and surface characteristics of these coatings were evaluated. And osteogenic effect of TiN and TiAlN coating on MG63 osteoblast-like cell proliferation and differentiation was evaluated by cell viability assay (MTT assay), ALP activity assay and expressions of collagen gene. Results As observed by SEM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Another study pointed out that TiN coating of Ti plasma sprayed implants exhibited a good affinity for primary human bone marrow mesenchymal stem cells in terms of adhesion, proliferation, and osteogenic differentiation. Jang et al [ 48 ] investigated the effect of TiN and TiAlN produced by physical vapor deposition on Ti dental implants upon MG63 cell behaviour. The analysis of the osteoblast proliferation and differentiation indicated a high level of biocompatibility of the treated Ti dental implant.…”
Section: Introductionmentioning
confidence: 99%
“…Another study pointed out that TiN coating of Ti plasma sprayed implants exhibited a good affinity for primary human bone marrow mesenchymal stem cells in terms of adhesion, proliferation, and osteogenic differentiation. Jang et al [ 48 ] investigated the effect of TiN and TiAlN produced by physical vapor deposition on Ti dental implants upon MG63 cell behaviour. The analysis of the osteoblast proliferation and differentiation indicated a high level of biocompatibility of the treated Ti dental implant.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of wear debris causes bone resorption, jeopardizing the long-term stability of the prosthesis [9,10]. Therefore, to improve the mechanical properties of Ti-6Al-4V, a variety of surface modifications have been utilized including nitrogen implantation and ultra-passivation of titanium [11]. These methods have become a standard procedure for Ti alloys.…”
mentioning
confidence: 99%
“…Wang [36] and Naghibi et al [37] reported the (220) preferred orientation of TiN coating at 2 θ = 61.36° on the steel and NiTi substrates, while other researchers [26,38,39] reported the (111) preferred direction at 2 θ = 36.42°. In the current study, it is hard to decide on the preferred orientation of TiN coating in these samples due to the sharp peaks of NiTi in the patterns.…”
Section: Resultsmentioning
confidence: 99%